Tingkat Kepuasan Kerja Dilihat Dari Perspektif Lingkungan Kerja Sosial dan Pengembangan Karir - Nurdini, Atin; Sumiyati, Sumiyati; Purnama, Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The purpose of this study was to find out the influence of social work environment on job satisfaction, the influence of career development on job satisfaction, and the influence of social work environment and career development on job satisfaction. Object of analysis in this research is employees of government service. This type of research is using verificative with explanatory survey method of 106 respondents. This study indicates that the influence of the social work environment to job satisfaction are included in the low category. Career development included in medium category to job satisfaction. The influence of social work environment and career development on job satisfaction is medium category. The results of the present study suggest if social work environment in conducive conditions, then it will increase job satisfaction. The implementation of career development is good, then job satisfaction will increase. In addition if social work environmental conditions are conducive and implementation of career development is good, then the job satisfaction will increase.